Pengembangan Souvenir Berbahan Kertas Koran Berupa Lukisan Wayang Beber Di Surakarta - Zarkasi, Much. Sofwan (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2013)
Firstly, the basic idea of this study, is an awareness of the presence of associated opportunities creativity and eksperimentation in the handicraft products made from waste newspapers materil collaburated with artwork tradition, that is wayang beber, as a unique selling point that can increase the sale valueÂ  of handicraft products. The novelty in this research is twofold : 1) to study this form of visual materials and techniques used in the manufacture of wayang beber image are different than usually the process of working on image wayang beber is using tradition techniques â€œsunggingâ€ that is painting techniques using natural dyes as well as the manufacturer, so in this study, art works of wayang beber made with collage technique, it is a technique using glue stick and newspapers and without any dye. 2) until now the souvenir or craft art with materials such as newspaper products wayang beber artworks using waste newspaper material on canvas has never existed.Keywords : wayangbeber, souvenir, newspaper